Tetraphenylporphyrin picks up zinc atoms from a silver surface - Kretschmann, Andreas; Walz, Marie-Madeleine; Flechtner, Ken; Steinrück, Hans-Peter; Gottfried, Michael (Chemical Communications, 2007)
We demonstrate that adsorbed meso-tetraphenylporphyrin molecules can coordinate Zn atoms that are pre-deposited on an Ag(111) surface, forming a complex that is identical to directly deposited tetraphenylporphyrinato-zinc(ii) ; this reaction, which we studied with XPS, is the first example of an oxidative dissolution of a metal by a large organic ligand under ultrahigh vacuum conditions. © The Royal Society of Chemistry.
UnivIS-Import:2015-04-14:Pub.2007.nat.dchph.lpc2.tetrap